The brain of Homo habilis: Three decades of paleoneurology. Issue 174 (January 2023) - Bruner, Emiliano; Beaudet, Amélie
Abstract: In 1987, Phillip Tobias published a comprehensive anatomical analysis of the endocasts attributed to Homo habilis, discussing issues dealing with brain size, sulcal patterns, and vascular traces. He suggested that the neuroanatomy of this species evidenced a clear change toward many cerebral traits associated with our genus, mostly when concerning the morphology of the frontal and parietal cortex. After more than 30 years, the fossil record associated with this taxon has not grown that much, but we have much more information on cranial and brain biology, and we are using a larger array of digital methods to investigate the paleoneurological variation observed in the human genus. Brain volume, the size of the frontal lobe, or the gross hemispheric asymmetries are still relevant issues, but they are considered to be less central than before. More attention is instead being paid to the cortical organization, the relationships with the cranial architecture, and the influence of molecular or ecological factors. Although the field of paleoneurology can currently count on a larger range of tools and principles, there is still a general lack of anatomical information on many endocranial traits. This aspect is probably crucial for the agenda of paleoneurology. More importantly, the whole science is undergoing a delicate change, because of the growing influence of the social environment. In this sense, the disciplines working with fossils (and, in particular, with brain evolution) should take particular care to maintain a healthy professional situation, avoiding an excess of speculation and overstatement.